First report of junctional epidermolysis bullosa (JEB) in the Italian draft horse - Cappelli, Katia (BMC Vet Res, 2015)
BACKGROUND: Epitheliogenesis imperfecta in horses was first recognized at the beginning of the 20th century when it was proposed that the disease could have a genetic cause and an autosomal recessive inheritance pattern. Electron microscopy studies confirmed that the lesions were characterized by a defect in the lamina propria and the disease was therefore reclassified as epidermolysis bullosa. Molecular studies targeted two mutations affecting genes involved in dermal–epidermal junction: an insertion in LAMC2 in Belgians and other draft breeds and one large deletion in LAMA3 in American Saddlebred. CASE PRESENTATION: A mechanobullous disease was suspected in a newborn, Italian draft horse foal, which presented with multifocal to coalescing erosions and ulceration on the distal extremities. Histological examination of skin biopsies revealed a subepidermal cleft formation and transmission electron microscopy demonstrated that the lamina densa of the basement membrane remained attached to the dermis. According to clinical, histological and ultrastructural findings, a diagnosis of junctional epidermolysis bullosa (JEB) was made. Genetic tests confirmed the presence of 1368insC in LAMC2 in the foal and its relatives. CONCLUSION: This is the first report of JEB in Italy. The disease was characterized by typical macroscopic, histologic and ultrastructural findings. Genetic tests confirmed the presence of the 1368insC in LAMC2 in this case: further investigations are required to assess if the mutation could be present at a low frequency in the Italian draft horse population. Atypical breeding practices are responsible in this case and played a role as odds enhancer for unfavourable alleles. Identification of carriers is fundamental in order to prevent economic loss for the horse industry.